2016
DOI: 10.4103/0971-9784.191562
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for blood conservation in pediatric cardiac surgery

Abstract: Cardiac surgery accounts for the majority of blood transfusions in a hospital. Blood transfusion has been associated with complications and major adverse events after cardiac surgery. Compared to adults it is more difficult to avoid blood transfusion in children after cardiac surgery. This article takes into account the challenges and emphasizes on the various strategies that could be implemented, to conserve blood during pediatric cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Intraoperative cell salvage has been shown to be a very safe and effective technique in reducing postoperative allogeneic blood transfusion and associated cost in pediatric cardiac surgical patients. 14,[46][47][48][49] Intraoperative cell salvage was not feasible for a long time in pediatric patients due to technical limitations mostly related to small volume of shed blood to be expeditiously processed for transfusion. There has been new generation of pediatric autotransfusion devices with small volume centrifugal bowls (49-55 mL) which will allow efficient blood salvage with hematocrit product ranging from 44% to 81% in small children.…”
Section: Operative Stagementioning
confidence: 99%
“…Intraoperative cell salvage has been shown to be a very safe and effective technique in reducing postoperative allogeneic blood transfusion and associated cost in pediatric cardiac surgical patients. 14,[46][47][48][49] Intraoperative cell salvage was not feasible for a long time in pediatric patients due to technical limitations mostly related to small volume of shed blood to be expeditiously processed for transfusion. There has been new generation of pediatric autotransfusion devices with small volume centrifugal bowls (49-55 mL) which will allow efficient blood salvage with hematocrit product ranging from 44% to 81% in small children.…”
Section: Operative Stagementioning
confidence: 99%
“…3,4 Studies have shown that the use of an autotransfusion device can significantly reduce donor red cell and coagulant product transfusion while also providing cost savings during cardiac surgery within the pediatric population. 59…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Studies have shown that the use of an autotransfusion device can significantly reduce donor red cell and coagulant product transfusion while also providing cost savings during cardiac surgery within the pediatric population. [5][6][7][8][9] There are several devices available for cell salvage and each has distinct features and advantages within a pediatric cardiac surgical practice. The three that were selected for this comparison were the Sorin Xtra ® (LivaNova USA Inc, Arvada, CO), Fresenius Continuous Autotransfusion System (CATS ®plus ) (Fresenius Kabi AG, Hamburg, Germany) and Fresenius CATSmart ® (Fresenius Kabi AG, Hamburg, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these challenges, it is increasingly recognized that many children with CHD, however vulnerable, can be safely managed with conservative blood management practices. 4 Anemia in pediatric cardiac surgery is primarily related to hemodilution from CPB priming solutions, intravenous fluids, coagulation status changes and operative bleeding. Anemia tolerance, bleeding risk and transfusion therapy are influenced by various factors including patient age and weight, surgical complexity, operative duration, degree of cyanosis and coagulopathies induced by CPB.…”
Section: Introductionmentioning
confidence: 99%